Community assembly of ectomycorrhizal fungi along a subtropical secondary forest succession. Issue 2 (9th October 2014) - Gao, Cheng; Zhang, Yu; Shi, Nan‐Nan; Zheng, Yong; Chen, Liang; Wubet, Tesfaye; Bruelheide, Helge; Both, Sabine; Buscot, François; Ding, Qiong; Erfmeier, Alexandra; Kühn, Peter; et al.
Summary Environmental selection and dispersal limitation are two of the primary processes structuring biotic communities in ecosystems, but little is known about these processes in shaping soil microbial communities during secondary forest succession. We examined the communities of ectomycorrhizal (EM) fungi in young, intermediate and old forests in a Chinese subtropical ecosystem, using 454 pyrosequencing. The EM fungal community consisted of 393 operational taxonomic units (OTUs), belonging to 21 EM fungal lineages, in which three EM fungal lineages and 11 EM fungal OTUs showed significantly biased occurrence among the young, intermediate and old forests. The EM fungal community was structured by environmental selection and dispersal limitation in old forest, but only by environmental selection in young, intermediate, and whole forests. Furthermore, the EM fungal community was affected by different factors in the different forest successional stages, and the importance of these factors in structuring EM fungal community dramatically decreased along the secondary forest succession series. This study suggests that different assembly mechanisms operate on the EM fungal community at different stages in secondary subtropical forest succession.